2011
DOI: 10.1002/jrs.2675
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of hydrogen‐arsenate group (AsO3OH) in solid‐state compounds: cobalt mineral phase burgessite Co2(H2O)4[AsO3OH]2·H2O

Abstract: Raman spectrum of burgessite, Co 2 (H 2 O) 4 [AsO 3 OH] 2 · H 2 O, was studied, interpreted and compared with its infrared spectrum.The stretching and bending vibrations of (AsO 3 ) and As-OH units, as well as the stretching, bending and libration modes of water molecules and hydroxyl ions were assigned. The range of O-H· · ·O hydrogen bond lengths was inferred from the Raman and infrared spectra of burgessite. The presence of (AsO 3 OH) 2− units in the crystal structure of burgessite was proved, which is in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
4
13
0
1
Order By: Relevance
“…Here, we found that the Raman spectra of the studied minerals below 1000 cm −1 perfectly illustrate the number of the present crystallographically different AsO 4 and AsO 3 OH units in their structures and it might serve as an indicator to deduce the number of these units for each mineral ( Figure 5). In accordance with the tentative assignments found in great number of published articles for Raman spectral behavior of hydrogen arsenate minerals, [3,[10][11][12][13][14][15][16][17]25] the highest wavenumber bands are attributed to antisymmetric ν 3 (AsO 3 OH) modes followed by one or two stronger bands from symmetric ν 1 (AsO 3 OH) modes at somewhat lower wavenumbers. These bands in the pharmacolite mineral, which consist of structurally equivalent (AsO 3 OH) 2− units, [6] were registered at 891, 862, and 841 cm −1 (Figure 5a) bearing close resemblance with their position in literature data (Table 3).…”
Section: (Aso 3 Oh) 2− and (Aso 4 ) 3− Vibrationssupporting
confidence: 75%
See 2 more Smart Citations
“…Here, we found that the Raman spectra of the studied minerals below 1000 cm −1 perfectly illustrate the number of the present crystallographically different AsO 4 and AsO 3 OH units in their structures and it might serve as an indicator to deduce the number of these units for each mineral ( Figure 5). In accordance with the tentative assignments found in great number of published articles for Raman spectral behavior of hydrogen arsenate minerals, [3,[10][11][12][13][14][15][16][17]25] the highest wavenumber bands are attributed to antisymmetric ν 3 (AsO 3 OH) modes followed by one or two stronger bands from symmetric ν 1 (AsO 3 OH) modes at somewhat lower wavenumbers. These bands in the pharmacolite mineral, which consist of structurally equivalent (AsO 3 OH) 2− units, [6] were registered at 891, 862, and 841 cm −1 (Figure 5a) bearing close resemblance with their position in literature data (Table 3).…”
Section: (Aso 3 Oh) 2− and (Aso 4 ) 3− Vibrationssupporting
confidence: 75%
“…However, the band assignment can be inferred from the pharmacolite discussion and following the previously published literature results from structurally similar hydrogen arsenate minerals. [10][11][12][13][14][15][16][17] The strongest maximum at 3542 cm −1 originates from OH stretchings of the non-hydrogen-bonded (or only weakly hydrogen bonded) OH oscillators of the water molecule. The shoulder appearing at about 3500 as well as the band at 3216 cm −1 may be attributed to the same mode, whereas the bands at 3055 and 2954 cm −1 (Figure 1d) are primarily attributed to the OH stretchings of the OH oscillator within the hydrogen arsenate molecular anion as well as from the OH stretchings from the hydrogen-bonded water molecules (Table 2).…”
Section: Oh Vibrations From Aso 3 Oh Groups and From Water Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous studies on a variety of arsenate minerals and compounds, especially those containing the AsO 3 OH groups, by means of infrared and Raman spectroscopic techniques (e.g., Mihajlović et al 2004, Đorđević & Karanović 2008, 2011a, 2011b, Čejka et al 2011. We present our Raman spectroscopic measurements of vladimirite in Figure 3.…”
Section: Raman Spectramentioning
confidence: 99%
“…Raman spectroscopy has proven most useful for the study of mineral structures [14][15][16][17][18][19]. The objective of this research is to report the Raman and infrared spectra of vantasselite and to relate the spectra to the molecular structure of the minerals.…”
Section: Introductionmentioning
confidence: 99%